1986
DOI: 10.1039/c39860000643
|View full text |Cite
|
Sign up to set email alerts
|

Co(CO)3NO encapsulated in zeolite NaY; a novel shape-selective Fischer–Tropsch catalyst

Abstract: The sorption of the title compound into the pores of NaY zeolite is studied by i.r. and 13C magic angle spinning n.m.r. spectroscopy; after appropriate activation, the supported cobalt system is a shape-selective catalyst for the hydrogenation of carbon monoxide to alkenes with a cut-off at Cg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, other observations for metal clusters inside zeolite cages have shown that the product formation is tailed off at hydrocarbon number around C5-C9 (Mc-Mahon et al, 1987;Nazar et al, 1983;Nijs et al, 1979; Ungar and Baird, 1986). The sharp tailoff at the carbon number above C9 is attributed to the shape-selective effect (McMahon et al, 1987;Ungar and Baird, 1986), since the C9 length fits the supercage diameter. However, it is known that the chain length of hydrocarbons is not limited to the pore size of the zeolite, at least for the linear hydrocarbons (Eic and Ruthven, 1988;Karger et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…However, other observations for metal clusters inside zeolite cages have shown that the product formation is tailed off at hydrocarbon number around C5-C9 (Mc-Mahon et al, 1987;Nazar et al, 1983;Nijs et al, 1979; Ungar and Baird, 1986). The sharp tailoff at the carbon number above C9 is attributed to the shape-selective effect (McMahon et al, 1987;Ungar and Baird, 1986), since the C9 length fits the supercage diameter. However, it is known that the chain length of hydrocarbons is not limited to the pore size of the zeolite, at least for the linear hydrocarbons (Eic and Ruthven, 1988;Karger et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the resulting product distribution shape correlated with the size distribution shape of these groups (presumed Gaussian). The nature of the above-mentioned spatial restriction differs-for heterogeneous Fischer-Tropsch catalysts, that is, the size of micro-or meso-pores of catalyst supports [30,31], especially zeolites with the 3D structure of channels (shape selectivity [32][33][34][35]). This field of Fischer-Tropsch catalysis, however, nowadays, is nearly abandoned (because of the generally low activity of shape-selective systems).…”
Section: Features Of Formation Of Long-chain Alkanes and Alcoholsmentioning
confidence: 99%
“…with a transfer line that was heated only to a temperature that is consistent with the cut-off of products being due to vapor pressure effects rather than metal crystallite size. A consideration of other data (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) show that the selectivities were most likely due to operational rather than F.-T. mechanistic factors.…”
Section: Positive Deviation At Higher Carbon Numbersmentioning
confidence: 99%